Regional differences in phylogenetic group of strains isolated from children with urinary tract infection in Korea - Ui-Yoon Choi; Seung Beom Han; Soo Young Lee; Jin Han Kang; Sun Mi Kim; Sang Hyuk Ma (Korean Pediatric Society, 2012)
PurposeWe phylogenetically analyzed the Escherichia coli strains isolated from children with urinary tract infection (UTI) in 2 regions of Korea. Virulence factors (VFs) and antibiotic resistance of the strains were also determined to compare the possible differences.MethodsA total of 138 E. coli strains were collected from the 2 regions; Gyeongin (78 strains) and Gyeongnam (60 strains). The phylogenetic groups were determined using the triplex polymerase chain reaction (PCR) method and multiplex PCRs were used to detect 7 VFs genes (fimH, papC, iutA, hlyA, sfa/focDE, afa/draBC, and kpsMT II). We also tested for antibiotic resistance.ResultsPhylogenetic groups, B2 (61.6%) and D (26.8%), comprised the majority of all isolated strains. Regional comparisons revealed that more B2 strains and fewer non-B2 (A+B1+D) strains were found in Gyeongnam, than in the Gyeongin region (P=0.033), and certain VFs were predominantly detected in Gyeongnam (P<0.05). Neither regional nor phylogenetic differences, in antibiotic resistance of the strains, were significant.ConclusionWe were able to confirm that the geographic location is an important determinant of the distribution of the phylogenetic groups and VFs among the E. coli strains that cause UTI in children.